Humanismus in der deutschen Literatur des Mittelalters und der Frühen Neuzeit : XVIII. Anglo-German Colloquium Hofgeismar 2003 - McLelland, Nicola, 1970-; Schiewer, Hans-Jochen; Schmitt, Stefanie, 1974- (Max Niemeyer, 2008)
The articles assembled here discuss humanism as a concept and phenomenon in the literature of the Middle Ages and the early modern age. With reference to authors, genres, and various reception phenomena, the authors set out to identify a humanistic matrix in 15th and 16th century German literature with a view to confirming or problematizing the concept as a signature of the epoch. The suitability of the term humanism as an epistemic category is subjected to searching scrutiny and discussed against the background of a broad literary spectrum with consistent reference to interrelations with the.